PENGARUH GAYA BELAJAR DAN MINAT BELAJAR TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XI IIS DI SMA NEGERI 7 SURAKARTA TAHUN AJARAN 2015/2016 - Dewi Maulia Setyaningsih; Mintasih Indriayu; Salman Alfarisy Totalia (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The objective of research were to find out the effect of learning styles and learning interest simultaneously towards economic lesson achievement in XI grade in SMA Negeri 7 Surakarta academic year 2015/2016. The method used desciptive quantitative method . The sample were 62 students of XI grade in SMA Negeri 7 Surakarta academic year 2015/2016. The data collection techniques used questionnaires. The data were analyzed by using multiple regression analysis. The results showed that there was a significant positive effect of of learning styles and learning interest variables simultaneously towards economic lesson achievement in XI grade in SMA Negeri 7 Surakarta academic year 2015/2016. The magnitude of the effect of learning styles and learning interest toward economic lesson achievement simultaneously obtained from the calculation of the R- square of 49,9%.